Promoting engagement in physical activity in early rheumatoid arthritis: A proof‐of‐concept intervention study. (14th July 2020) - Cramp, Fiona; Thomas, Rachel; Haase, Anne M.; Domaille, Melissa; Manns, Sarah; Swales, Caroline; Hurfurt, Judy; Walsh, Nicola E.
Abstract: Objective(s): The aim of this study is to test the feasibility and acceptability of promoting engagement in physical activity in early rheumatoid arthritis (PEPA‐RA) to inform a future trial. Design: A 'proof of concept' study was carried out. Setting: This study was conducted in community hospitals delivered by musculoskeletal primary care physiotherapists. Participants: Participants were 12 adults with rheumatoid arthritis (RA) diagnosed 6–24 months previously (nine females, three males; mean age 58 years, range 23–79). Intervention: The intervention consisted of five sessions, that is, four group sessions and one individual session facilitated by a physiotherapist over 12 weeks including patient education and support for behaviour change as well as supervised practical exercise. Main outcomes: The main outcomes were attendance, completion of outcome measures, adverse events, and participant and physiotherapist feedback views relating to the intervention. Results: Overall attendance was 85%, with sessions missed due to illness or RA flare. Outcome measure completion ranged from 83% to 100%. There were no clinically meaningful changes in pain or function at 12 weeks, but mean 6‐min walk distance improved from 394 to 440 m. No serious adverse events were reported, and participants were generally positive about the intervention. Suggested minor modifications for the group sessions included venue accessibility and ensuring that physical activity time was protected. Several participants indicated that they would have liked to receive the intervention earlier following diagnosis. Conclusions: PEPA‐RA and the outcomes appear feasible and acceptable. Overall, small beneficial effects were noted at 12 weeks for most outcomes. Challenges to recruitment resulted in a smaller than anticipated sample size, and the majority of participants were active at baseline indicating that future recruitment needs to target less active individuals.